New exact solutions for the ZK-MEW equation by using symbolic computation - İnç, Mustafa (Elsevier Science Inc, 2007)
In this paper, the extended tanh-method is used to establish exact travelling wave solutions of the Zakharov-Kuznetsov-Modified Equal-Width (ZK-MEW) equation. The obtained solutions include solitary wave solutions, periodic wave solutions and combined formal solutions. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: extended tanh-method; ZK-MEIM equation; solitons; symbolic computation